Utilization of Secang Wood Ethanol Extract (Caesalpinia sappan L.) as an Additional Ingredient Antiseptic Hand Cream Preparations Instead of Hand Sanitizer - Sari, Nurmala; Inayah, Nurul (Indonesian Journal of Chemical Research, 2023)
Secang wood is a plant used in medicine. This study aims to find out that ethanol extract of secang wood can be formulated into a hand cream preparation and to determine the antibacterial activity against Staphylococcus aureus as an antiseptic. This study used the maceration method to produce ethanol extract, then made a hand cream dosage formula using 2, 4, and 6% ethanol extract of secang wood. Then a physical quality evaluation is carried out including organoleptic testing, homogeneity testing, pH measurement, viscosity testing, and dispersion power. After that, an antiseptic test of Staphylococcus aureus is carried out. Based on research, the results show that hand cream preparations meet the standards. The anti-bacterial activity test of the hand cream extract of wood ethanol extract can inhibit the growth of Staphylococcus aureus with a concentration of 2, 4, and 6% respectively by 13.1; 13.9 and 14.8 mm fall into the category of inhibitory solid zones.